A history of trumpet teachers at CSU - Barrett, Enzo, author (Colorado State University. Libraries, 2023)
Presentation given in November 2023 on the history of trumpet teachers at Colorado State University. Includes short biographies of Jake Larson, Barbara Prugh, Michael Chunn, Gil Garcia, David Shaner, Dan Kuehn, Steve Marx, Dawn Kramer, Caleb Hudson, and Stanley Curtis. Contains a complete timeline of the history of trumpet teachers at CSU constructed from directories in the CSU archives.
Student from Department of Music, supervised by Dr. Dawn Grapes.
Keywords: Trumpet; Professor; Instructor; Larson, Jake; Prugh, Barbara; Chunn, Michael; Garcia, Gil; Shaner, David; Kuehn, Dan; Marx, Steve; Kramer, Dawn; Hudson, Caleb; Curtis, Stanley; Sauer, Barbara